Grazing intensity contributes to cyanogenic toxicity in savannah grasses in Baringo county - Koskei, Alfayo; Maranga, Elias; Obonyo, Meshack (International Journal of Biological Research, 2016)
The potential role of anti-herbivory mechanisms used by plants and their synergistic responses to grazing and interactive effects on herbivores are poorly understood. The aim of this study was to quantify the influence of grazing intensity on cyanogenic glycosides in Lake Bogoria, Baringo County Kenya. Field experiments were carried out in ten 50Ã—10m enclosures. Grazing intensity was varied using simulated grazing method where two grazing treatments used; heavy grazing and light grazing. Grasses were categorized into two age classes; young and old. Cyanigenic glycocides (CNglc) were tested using impregnated picrate paper and their concentration determined by hydrolysis and trapping in 1M NaOH. Our findings showed that five of 16 sampled species produce cyanogenic glycosides; Cynodon dactylon, Cynodon plectostachyus, Digitaria scalarum, Sporobolus spicatus and Cyperus laevigatus. There was an inverse relation between Cyanide concentration and age of the plants. Young cuttings yield more Hydrogen Cyanide than older cuttings of the same grasses.Grazing intensity had a significant effect on the concentration of cyanogenic content in some grass species; C.dactylon (P=0.024) and S. laevigatus (P=0.003). The findings imply that grazing regime of managed pastures should consider the age of forage while allowing utilization of pastures preferably grazed on mature pastures with low levels of cyanogenic glycosides.